2016
DOI: 10.1007/s10620-016-4366-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness Is Not Associated with Adherence to Colorectal Cancer Screening: Results from the California Health Interview Survey

Abstract: Background Colorectal cancer is the second leading cause of cancer-specific death in the United States. Evidence suggests people with mental illness are less likely to receive preventive health services, including cancer screening. We hypothesized that mental illness is a risk factor for nonadherence to colorectal cancer screening guidelines. Methods We analyzed results of the 2007 California Health Interview Survey to test whether mental illness is a risk factor for non-adherence to colorectal cancer screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Three previous US population-based studies using the K6 scale demonstrated a nonsignificant association between PD and participation in colorectal cancer screening. 1,10,12 This inconsistency may be caused by differences in cancer screening systems, medical systems, or cultures. Further studies in other countries are needed to clarify the association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three previous US population-based studies using the K6 scale demonstrated a nonsignificant association between PD and participation in colorectal cancer screening. 1,10,12 This inconsistency may be caused by differences in cancer screening systems, medical systems, or cultures. Further studies in other countries are needed to clarify the association.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that individuals experiencing psychological distress (PD), such as depression or anxiety, are less likely to participate in cancer screening. According to our in-house, preliminary, systematic review, most population-based studies examining the associations between PD and screening for colorectal, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] breast, 1-6,10,14-21 or cervical cancers 1,3,10,15,[17][18][19][22][23][24] have been conducted in North America or Europe. One meta-analysis reported a significant reduction in mammography screening rates among women with mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have investigated particular types of cancer screening in people with SMI, but these were mostly conducted in specific populations and results may not be broadly generalisable (Howard et al, 2010). Furthermore, some studies used self-reported participation in screening, which may not be optimal in this population (Fujiwara et al, 2017; Howard et al, 2010; Mo et al, 2014; Siantz et al, 2017), while others had no comparison group (Howard et al, 2010; James et al, 2017). The aim of this study was to investigate the frequency of colorectal, prostate and cervical cancer screening among people with and without SMI, throughout Australia, using a large, nationally representative administrative data set of 10% of the Australian population.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Yee et al conducted a study with 606 female veteran participants aged 50 to 65 years and found that females with mental health disorders were as likely as females without mental disorders to undergo CRC screening [ 23 ]. Furthermore, a study based on the California Health Interview Survey, which included 15,535 individuals aged 50 years and above, found no association between mental disorders and CRC screening [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing research on the link between mental disorders and CRC screening has produced mixed and inconclusive results. While some studies suggest that individuals with mental disorders have lower rates of CRC screening compared to the general population, others have found no significant correlation between mental health status and screening for CRC [ 10 , 13 - 15 ]. This inconsistency emphasizes the need for further research to clarify the relationship and identify contributing factors.…”
Section: Introductionmentioning
confidence: 99%